ANALYSIS OF DIDACTIC VALUES IN THE TEACHER’S DIARY BY NITHIWAT THARATHORN - Muhamad Yusuf; Trie Utari Dewi (Universitas Indraprasta PGRI, 2020)
Abstract: The Teacher’s Diary film by Nithiwat Tharathorn raises the theme of the struggle of teachers who teach in remote school. The problem discussed in this research is didactic value. The researcher describes the didactic values found in the depiction of characters through actions, speech and mind. Didactic value analysis in this film used Ali's theory. The method used is descriptive qualitative content analysis approach. The results showed that the didactic values contained in the film The Teacher's Diary, namely intellectual / intelligence value, skill value, self-esteem value, social values / community relations / association, moral value, beauty value, divine / religious value, self-control value / emotional stability, value of behavior / customs of courtesy, the value of will / desire or ideals. Based on the research results, it can be concluded that the didactic values in this film can be used as a reflection or example for teachers to teach and educate students and understand the meaning of teacher in a complete perspective. Keywords: Didactic Value, The Teacher’s Diary, Film.